Contactless steering of a plasma jet with a 3D magnetic nozzle. (4th August 2017) - Merino, Mario; Ahedo, Eduardo
Abstract: A 3D, steerable magnetic nozzle (MN) is presented that enables contactless thrust vector control of a plasma jet without any moving parts. The concept represents a substantial simplification over current plasma thruster gimbaled platforms, and requires only a small modification in thrusters that already have a MN. The characteristics of the plasma expansion in the 3D magnetic field and the deflection performance of the device are characterized with a fully magnetized plasma model, suggesting that thrust deflections of 5° –10° are readily achievable.